Pneumococcal Pyopericardium With Xiphoid Osteomyelitis in HIV/AIDS: A Rare but Potentially Fatal Complication - Nihar Jena; Izza Saeed; Mackenzie Hamilton; Christian Tocquica; Sreekant Avula; Ramiz Sayyed; Juan Bastidas; Mark Studeny (Case Reports in Cardiology)
Conclusion: This case illustrates an unusual presentation of HIV-AIDS, highlighting advancements in managing pneumococcal pyopericardium with tamponade and the ongoing risk of opportunistic infections despite antiretroviral treatment. Though rare, pyopericardium can be fatal; so prompt diagnosis and multidisciplinary management are essential to improve outcomes.